Applications of Derivatives Made Easy - Deepak Bhardwaj (Firewall Media/ Laxmi Publications, 2007)
This book has been divided into seven chapters. In each chapter, all concepts and definitions have been discussed in detail. A large number of well-graded solved examples are given in each chapter to illustrate the various concepts and methods. The remarks and notes have been added quite often in the book so that they may help in understanding the ideas in a better way. At the end of each chapter, a short exercise has been incorporated for the quick revision of the chapter. All solutions have been written in simple and lucid language. The book will guide the students in a proper way and inspire them to sure and brilliant success. The book serves the purpose of text as well as a help book.